Combinatorial treatments of tamoxifen with SM6Met, a selective estrogen receptor subtype modulator (SERSM), from Cyclopia subternata are superior to current endocrine treatments in breast cancer cell models. - Van Dyk, Lorinda (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.